Impact of potential pregabalin or duloxetine drug–drug interactions on health care costs and utilization among Medicare members with fibromyalgia - Ellis JJ; Sadosky AB; Ten Eyck LL; Cappelleri JC; Brown CR; Suehs BT; Parsons B (Dove Medical Press, 2014)
Jeffrey J Ellis,1 Alesia B Sadosky,2 Laura L Ten Eyck,1 Joseph C Cappelleri,2 Courtney R Brown,3 Brandon T Suehs,1 Bruce Parsons2 1Comprehensive Health Insights Inc., Louisville, KY, USA; 2Pfizer Inc., New York, NY, USA; 3Humana Inc., Louisville, KY, USA Purpose: To examine the impact of newly initiated pregabalin or duloxetine treatment on fibromyalgia (FM) patients' encounters with potential drug–drug interactions (DDIs), the health care cost and utilization consequences of those interactions, and the impact of treatment on opioid utilization.Patients and methods: Subjects included those with an FM diagnosis, a pregabalin or duloxetine prescription claim (index event), ≥1 inpatient or ≥2 outpatient medical claims, and ≥12 months preindex and ≥6 postindex enrollment. Propensity score matching was used to help balance the pregabalin and duloxetine cohorts on baseline demographics and comorbidities. Potential DDIs were defined based on Micromedex 2.0 software and were identified by prescription claims.Results: No significant differences in baseline characteristics were found between matched pregabalin (n=794) and duloxetine cohorts (n=794). Potential DDI prevalence was significantly greater (P<0.0001) among duloxetine subjects (71.9%) than among pregabalin subjects (4.0%). There were no significant differences in all-cause health care utilization or costs between pregabalin subjects with and without a potential DDI. By contrast, duloxetine subjects with a potential DDI had higher mean all-cause costs ($9,373 versus $7,228; P<0.0001) and higher mean number of outpatient visits/member (16.0 versus 13.0; P=0.0009) in comparison to duloxetine subjects without a potential DDI. There was a trend toward a statistically significant difference between pregabalin and duloxetine subjects in their respective pre- versus post-differences in use of ≥1 long-acting opioids (1.6% and 3.4%, respectively; P=0.077).Conclusion: The significantly higher prevalence of potential DDIs and potential cost impact found in FM duloxetine subjects, relative to pregabalin subjects, underscore the importance of considering DDIs when selecting a treatment.Keywords: Cymbalta, morphine equivalents, Lyrica